2019
DOI: 10.3892/ijo.2019.4915
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of GHSR, GNG4, HOXD9 and SALL3 is a common epigenetic alteration in thymic carcinoma

Abstract: Thymic epithelial tumors comprise thymoma, thymic carcinoma and neuroendocrine tumors of the thymus. Recent studies have revealed that the incidence of somatic non-synonymous mutations is significantly higher in thymic carcinoma than in thymoma. However, limited information is currently available on epigenetic alterations in these types of cancer. In this study, we thus performed genome-wide screening of aberrantly methylated CpG islands in thymoma and thymic carcinoma using Illumina HumanMethylation450 K Bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
3
24
1
Order By: Relevance
“…HOXB2, B3, B4, B7 and B9 genes which we observed their upregulation in association with endometriosis, was previously shown that are in contribution with endometriosis, and also are involved in progression and development of many cancers [27,[31][32][33][34][35][36][37][38][39]. About HOXC6, C8, C9, C10, C11, C12 and C13 genes which were analyzed here, no other studies have paid attention to the relationship between these genes and endometriosis, although their involvement with female reproductive tract are vastly shown [29].…”
Section: Go Annotation Analysissupporting
confidence: 65%
“…HOXB2, B3, B4, B7 and B9 genes which we observed their upregulation in association with endometriosis, was previously shown that are in contribution with endometriosis, and also are involved in progression and development of many cancers [27,[31][32][33][34][35][36][37][38][39]. About HOXC6, C8, C9, C10, C11, C12 and C13 genes which were analyzed here, no other studies have paid attention to the relationship between these genes and endometriosis, although their involvement with female reproductive tract are vastly shown [29].…”
Section: Go Annotation Analysissupporting
confidence: 65%
“…Some studies have shown that high expression of HOXA10-AS in lung adenocarcinoma [46] and glioma [47] can promote tumor progression. According to the risk model, hypermethylation and low expression of HOXA10-AS can increase patient survival risk, which may be related to the heterogeneity of different [48] found that promoter methylation of HOXD9 was significantly higher in thymic carcinoma than in thymoma and the thymus, and relapse-free survival was significantly worse in tumors with a higher DNA methylation of HOXD9 in all of the thymic epithelial tumors. Similar to the results of this study, hypermethylation of HOXD9 was positively correlated with high risk score.…”
Section: Discussionmentioning
confidence: 99%
“…Petrini et al (14) demonstrated that GTF2IL424H mutations were the most common in type A and AB thymomas. Limited information is currently available on epigenetic alterations in TET (15)(16)(17)(18). We previously reported that the aberrant methylation of 4 cancer-related genes (DAPK, p16, MGMT, and HPP1) was significantly more frequent in TC than in thymomas (15,16).…”
Section: Gad1 Expression and Its Methylation As Indicators Of Malignant Behavior In Thymic Epithelial Tumorsmentioning
confidence: 99%